Controlled Bioactive Delivery Using Degradable Electroactive Polymers - Ashton, Mark D.; Cooper, Patricia A.; Municoy, Sofia; Desimone, Martin F.; Cheneler, David; Shnyder, Steven D.; Hardy, John G. (Biomacromolecules, 2022)
Biomaterials capable of precisely controlling the delivery of agrochemicals/biologics/drugs/fragrances have significant markets in the agriscience/healthcare industries. Here, we report the development of degradable electroactive polymers and their application for the controlled delivery of a clinically relevant drug (the anti-inflammatory dexamethasone phosphate, DMP). Electroactive copolymers composed of blocks of polycaprolactone (PCL) and naturally occurring electroactive pyrrole oligomers (e.g., bilirubin, biliverdin, and hemin) were prepared and solution-processed to produce films (optionally doped with DMP). A combination of in silico/in vitro/in vivo studies demonstrated the cytocompatibility of the polymers. The release of DMP in response to the application of an electrical stimulus was observed to be enhanced by ca. 10–30% relative to the passive release from nonstimulated samples in vitro. Such stimuli-responsive biomaterials have the potential for integration devices capable of delivering a variety of molecules for technical/medical applications.